2007
DOI: 10.11646/zootaxa.1465.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Egg morphology update based on new chorionic data of Potamanthus luteus  (Linnaeus), Ephemera danica Müller and Oligoneuriella rhenana (Imhoff) (Insecta, Ephemeroptera) obtained by scanning electron microscopy

Abstract: The chorionic patterns of Ephemeroptera eggs are very diverse and these have often been used for taxonomic and systematic purposes. In a great number of species, including Potamanthus luteus, Ephemera danica and Oligoneuriella rhenana, these egg features have been studied using light microscopy. However, current trends in egg morphology studies use scanning electron microscopy (SEM), so that the eggs of these species need to be re-described in order to establish morphological comparisons. The general chorionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…1995; Studemann and Landolt 1997). However, as in the case of the lateral attachment structures of the eggs of Potamanthus luteus (Linnaeus, 1767) (Potamanthidae), in which SEM studies revealed morphological characteristics that cannot be considered KCTs (Ubero‐Pascal and Puig 2007), the morphological characteristics of the lateral attachment structures of Ephemerellidae eggs also lead us to question the type to which they have traditionally been assigned.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1995; Studemann and Landolt 1997). However, as in the case of the lateral attachment structures of the eggs of Potamanthus luteus (Linnaeus, 1767) (Potamanthidae), in which SEM studies revealed morphological characteristics that cannot be considered KCTs (Ubero‐Pascal and Puig 2007), the morphological characteristics of the lateral attachment structures of Ephemerellidae eggs also lead us to question the type to which they have traditionally been assigned.…”
Section: Discussionmentioning
confidence: 99%
“…1987, 1993; Kluge et al . 1995; Klonowska‐Olejnik 1997; Klonowska‐Olejnik & Jazdzewska 2003; Ubero‐Pascal 2004; Ubero‐Pascal and Puig 2007), although the number of species in which they have been studied in depth is still low.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure and ultrastructure of insect egg capsules have been investigated by many authors (Biliński & Jankowska, ; Domínguez & Cuezzo, ; Gaino, Mazzini, Degrange, & Sowa, ; Gaino & Bongiovanni, ; Gaino & Mazzini, ; Gaino, Piersanti, & Rebora, ; Gaino, Sartori, & Rebora, ; Hinton, ; Kambysellis, Margaritis, & Craddock, ; Kaulenas et al, ; Kłonowska‐Olejnik & Jażdżewska, ; Krzysztofowicz & Kisiel, ; Margaritis, Kafatos, & Petri, ; Simiczyjew, ; Skudlik, Poprawa, & Rost, ; Ubero‐Pascal & Puig, ; Vogelgesang & Szklarzewicz, ; Wichard, Arens, & Eisenbeis, , b; Zawadzka, Jankowska, & Biliński, ). In the context of the great diversity of insects and their abilities to adapt to practically any environment on Earth, egg capsules, inside which the essential first step of development takes place continues to be of great interest.…”
Section: Introductionmentioning
confidence: 99%